The Role of Microcomputer Clubs in the Education of the Polish Youth in the 1980s: A Retrospective Analysis - Karol Król (MDPI AG, 2022)
In the 1980s, Polish schools hardly had access to computers, particularly at the primary and secondary levels. The main reasons were funds and shortage of qualified staff that could handle computer hardware. As a consequence, the youth first came across a computer, how to use it, service hardware, and write programs outside schools in the early 1980s. Often informal groups of hobbyists gathered around a single computer were the seeds of microcomputer clubs, which cropped up in huge numbers in Poland in the 1980s. The objective of the paper is to portray the role of microcomputer clubs in the process of shaping the youth and computer education in the 1980s in Poland compared to other countries. The conclusions are founded on a literature review. The analyzed material included an Internet Archive collection "The Computer Magazine Archives". The content of one of the first Polish computer magazines, Bajtek Magazine was analyzed in detail. It has been demonstrated that the Polish youth of the 1980s first came across a computer mainly outside schools, primarily in microcomputer clubs. It was the root of computer and information technology education in Poland. Moreover, microcomputer clubs were reported to provide education, as well as foster character education, aid socialization, and shape attitudes.